Formation of Gold Alloys during Crustal Differentiation of Convergent Zone Magmas: Constraints from an AU-Rich Websterite in the Stanovoy Suture Zone (Russian Far East) - Nikolai Berdnikov; Pavel Kepezhinskas; Natalia Konovalova; Nikita Kepezhinskas (Geosciences, 2022)
Gold is typically transported by mafic and evolved magmas into the upper crust to be deposited in shallow oxidized porphyry and epithermal environments. However, the magmatic behavior of gold is still poorly understood and warrants further attention. Additional insights into the magmatic evolution of gold and other noble metals can be provided by investigations of primitive convergent zone magmas and products of their differentiation that contain primary-textured Au-alloys. One of the best examples of such Au-rich ultramafic cumulates is the Triassic (232–233 Ma) Ildeus intrusion, which was emplaced within the Mesozoic Stanovoy subduction zone in the Russian Far East. Some websterites from the Ildeus intrusion, representing cumulates crystallized from a primitive convergent zone magma, are enriched in Au (up to 596 ppm) and contain abundant Cu-Ag-Au micro-particles. Most of these Au-alloy micro-particles display compositions similar to those previously found in explosive pyroclastic rocks in the Lesser Khingan iron district, mantle wedge peridotites in Kamchatka and Cretaceous adakites in the Stanovoy suture zone. Textural and compositional characteristics suggest that Cu-Ag-Au alloys precipitated from a primitive calc-alkaline melt during its crustal differentiation in a Mesozoic paleo-subduction zone. Some large Cu-Ag-Au grains display an internal honeycomb-like structure with alternating Cu-rich and Cu-poor zones. Heating experiments under atmospheric conditions recorded a substantial loss of Cu from primary magmatic Cu-Ag-Au alloys, which appears to be a process characteristic of oxidized hydrothermal ore systems. We suggest that the later-stage hydrothermal alteration of differentiated igneous conduits containing magmatic gold alloys results in the formation of Cu-free gold mineralization comparable to the upper crustal porphyry and epithermal environments.